2014
DOI: 10.3136/fstr.20.1109
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Tea Sample Preparation Methods for ICP-MS and Application to Verification of Chinese Tea Authenticity

Abstract: In this study, 35 black, oolong, and green tea samples from China were analyzed by inductively coupled plasma mass spectrometry after a digestion method was developed on the basis of a response surface methodology. Linear discriminant analysis of whole data sets was performed in order to discriminate and classify Chinese tea samples according to their origin and type. The analysis revealed an excellent separation between tea samples according to their type and origin with a discrimination efficiency of 100%. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…1990). The previous studies found the lead content in different tea types increase in order from green tea, to black tea, and oolong tea (Han et al, 2006(Han et al, , 2014. Moreover, the processing procedure and storage (e.g.…”
Section: Leadmentioning
confidence: 98%
“…1990). The previous studies found the lead content in different tea types increase in order from green tea, to black tea, and oolong tea (Han et al, 2006(Han et al, , 2014. Moreover, the processing procedure and storage (e.g.…”
Section: Leadmentioning
confidence: 98%
“…A total of 18 elements (Mg, Al, P, S, Cl, K, Ca, Mn, Fe, Cu, Zn, Br, Rb, Sr, Ni, Si, Ti and Sn), all showing good repeatability and accuracy results, were selected for further descriptive statistical and chemometrics analysis. Of these 18, 10 were used in the study of Han et al. (2014) and 13 were used in the study of Rajapaksha et al.…”
Section: Resultsmentioning
confidence: 99%
“…(2017) . Ni and Mn, which were the main elements in the discrimination of the tea samples in Han et al. (2014) , are included in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Tea has received increasing attention for its beneficial health properties that include the prevention of cardiovascular diseases, skin cancer, coronary artery disease, Parkinson's disease and myocardial infarction (Qin & Chen, 2007)). However, several studies have demonstrated that tea leaves may also contain some harmful contaminants, which can be released into infusions; such as, considerable levels of heavy metals including lead, cadmium, arsenic, mercury (Han, Mihara, & Fujino, 2014;Shaltout, Abdel-Aal, Welz, & Castilho, 2013), poly-chlorinated biphenyls (PCBs), fertilizers, pesticides (Beizhen, Weihua, Liping, & Tiefeng, 2008;Shen & Chen, 2008) and poly-aromatic hydrocarbons (PAHs) (Lin, Zhu, He, & Tu, 2006)) are reported in different types of tea infusions. Contaminated cultivation soils, transportation and possessing procedures are suggested as possible sources of these contaminants.…”
Section: Introductionmentioning
confidence: 99%